1985
DOI: 10.1042/bj2300465
|View full text |Cite
|
Sign up to set email alerts
|

Isolation from bovine elastic tissues of collagen type VI and characterization of its form in vivo

Abstract: Foetal-bovine nuchal ligament and aorta, together with adult-bovine aorta and pregnant uterus, were extracted under dissociative conditions in the absence and in the presence of a reducing agent. A collagenous glycoprotein of Mr 140000 [designated component 140K(VI)], identified in these extracts as the major periodate/Schiff-positive component, was shown to be related to collagen type VI. Digestion of non-reduced extracts with pepsin yielded periodate/Schiff-positive peptides that, on the basis of their elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1986
1986
1998
1998

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…The possible relationship between the secreted glycoprotein of Mr 140000 and 150000 and the 140K(VI) component of type VI collagen [12] was investigated by using a specific anti-(type VI collagen) antibody. Comparable experiments with anti-(microfibrillar protein) serum could not be carried out as this antiserum [3] is no longer available, and attempts in this and in other laboratories to produce an antiserum with similar specificity have been unsuccessful.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The possible relationship between the secreted glycoprotein of Mr 140000 and 150000 and the 140K(VI) component of type VI collagen [12] was investigated by using a specific anti-(type VI collagen) antibody. Comparable experiments with anti-(microfibrillar protein) serum could not be carried out as this antiserum [3] is no longer available, and attempts in this and in other laboratories to produce an antiserum with similar specificity have been unsuccessful.…”
Section: Resultsmentioning
confidence: 99%
“…for three determinations. Peptide ' mapping' was carried out on [3H]prolineand [3H]fucoselabelled components after digestion with Staphylococcus aureus V8 proteinase or CNBr [12].…”
Section: S Ayad and Othersmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this is less clear for type VI collagen. Several authors have extracted microfibrillar components of various soft connective tissues and analysed this material biochemically and microscopically ( 5 , 13,14). Although these studies demonstrated that the extracted microfibrillar structures contained or even consisted of type VI collagen, it was unclear whether the microfibrils originated from the oxytalan system.…”
mentioning
confidence: 99%